ENVIRONMENTAL SUSTAINABILITY AND SUSTAINABLE GROWTH RATE OF FIRMS. (Al-Aasar, 2025)
In the modern world, studying the environment is a complex task affected by many internal and external factors, including policies made by the government. The main focus of this study is on Pakistan. It looks at the link between how healthy the environment is and how fast businesses can grow in the long term.  The study focuses on non-financial companies and lasts for five years, from 2016 to 2020. It mainly looks into companies listed on the Pakistan Stock Exchange (PSX). The Panel Ordinary Least Squares regression model was used for this study because it is good at finding the complex link between environmental sustainability and sustainable growth rates. The results of this article show a strong link between environmental sustainability and companies' sustainable growth rates. The findings add to what is known about how environmental sustainability and business success are connected. They are helpful for both researchers and people who work in business and environmental studies.